Peran Data Science dan Data Scientist Untuk Mentransformasi Data Dalam Industri 4.0 - Syamsu, Muhajir; Widodo, Widodo (ITB Ahmad Dahlan Jakarta, 2021)
Technological developments in the era of the industrial revolution 4.0, which places the role of Data Science and Data Scientist as tools to transform data into very important data, plus the need for Data Science and Data Scientist, which is very much needed in the midst of Industry 4.0 and is able to accompany increasingly large digital data in its management. This research aims to find out how big the role of Data Science and Data Scientist in transforming data in industry 4.0. This study uses the Research Area Coverage method because this research has shifted from various fields of science, with a method design with the SISP (Strategic Information System Planning) approach using steps such as data collection, condition analysis and interpretation. The data collection technique in this research is a survey and case study approach which is conditioned by the facts or facts that occur in the field. The results of the study show that the role of Data Science and Data Scientist is very much needed in industry 4.0 to perform very large data processing, with the capabilities and skills possessed by Data Science and Data Scientist being able to accompany digital technology that develops in industry 4.0.